2014
DOI: 10.1017/jns.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise and diet on olfactory capability in detection dogs

Abstract: A previous work suggests that dietary fat may influence canine olfaction. The present study evaluated whether olfactory performance could be influenced by forms of dietary fat and exercise. Seventeen certified detection dogs were fed three different diets (high fat, low fat or high polyunsaturated fat) for 12 weeks. After 12 weeks, olfactory testing was performed using a scent wheel in an olfaction laboratory using three explosive materials. The dogs completed eight to twelve scent trials before and after a 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The rooms where the dogs ran were kept at 30% humidity and 72°F at all times. All data and sample collection occurred on day 3 of the 3 days of treadmill testing on week 12, while olfaction data were obtained on the other 2 days of exercise ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rooms where the dogs ran were kept at 30% humidity and 72°F at all times. All data and sample collection occurred on day 3 of the 3 days of treadmill testing on week 12, while olfaction data were obtained on the other 2 days of exercise ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings are similar to rodent studies which suggested that polyunsaturated fatty acids may affect olfaction positively by altering the olfactory bulb cellular constitution, thereby enhancing neuronal signaling ( 11 , 12 ). More recently, our lab reported that the use of corn oil improved the olfactory acuity at threshold concentrations in trained detection dogs showing that dietary fat and fat source can play a role in olfaction and/or cognition, yet the physiology of such improvements can only be speculated ( 13 ). Theoretically, dietary fat may offer an advantage of running with more thermodynamic efficiency compared to a higher protein, higher carbohydrate diets since there is less of a need for gluconeogenesis during exercise eliminating protein as a source of energy which is thermodynamically less efficient than fat or carbohydrate ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is insufficient knowledge to ascertain if the probability of canine alert to currency is determined by total chemically extractable cocaine on a bill or limited to superficial cocaine that can be removed by physical means such as vacuuming. With regard to interpretation of a particular canine alert based upon extrapolation from published studies, it is important to consider biological, behavioral, and environmental variables such as breed, training, drug type, search environment, handler cues and handler interpretation of canine responses, presearch exercise , and diet as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Sargisson and McLean found that the false alert rate for explosive detection is dependent on positive reinforcement. In addition, physiologic factors appear to affect canine alert such as presearch strenuous exercise and diet .…”
Section: Review and Analysis Of Scientific Literature On Canine Alertmentioning
confidence: 99%